AN ANALYSIS OF SELF-CONCEPT IN STUDENTS’ WRITING PERFORMANCE OF ENGLISH DEPARTMENT AT BBG UNIVERSITY - Rosdiana Rosdiana; Mulyadi Syahputra; Harfiandi (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Writing is a critical skill in English language instruction, encompassing cognitive, affective, and psychomotor domains. This study focuses on the affective domain, particularly the self-concept, and its influence on students' writing performance. The research analyzes self-concept as reflected in students' writing performance within the English Department of BBG University. A qualitative case study approach was employed, utilizing in-depth interviews, direct observation, and documentation. The findings revealed that students' self-concept could be categorized into academic self-concept, social self-concept, and personal self-concept. Positive self-concept was associated with higher confidence and better writing performance, often linked to previous achievements, interest in writing, and supportive environments. Conversely, negative self-concept was characterized by lack of confidence, fear of making mistakes, and blame on external factors. The study concludes that self-concept plays a significant role in shaping students' writing outcomes, highlighting the importance of fostering positive perceptions and using reflective tools like journals to enhance their performance. This research offers insights for educators to develop teaching strategies that address the affective needs of students, ultimately promoting confidence and skill development in academic writing.